The Bipedicled Orbicularis Oculi Myocutaneous Flap for the Repair of Paralytic Ectropion - Fleischman, Gitanjali M. (JAMA Facial Plast Surg, 2018)
This case series describes the bipedicled orbicularis oculi myocutaneous flap as a new surgical approach for paralytic eyelid syndrome.